H5N1 Vaccine–Elicited Memory B Cells Are Genetically Constrained by the IGHV Locus in the Recognition of a Neutralizing Epitope in the Hemagglutinin Stem - Wheatley, Adam K; Whittle, James R R; Lingwood, Daniel; Kanekiyo, Masaru; Yassine, Hadi M; Ma, Steven S; Narpala, Sandeep R; Prabhakaran, Madhu S; Matus-Nicodemos, Rodrigo A; Bailer, Robert T; Nabel, Gary J; Graham, Barney S; et al. (The Journal of immunology (1950), 2015)
Because of significant viral diversity, vaccines that elicit durable and broad protection against influenza have been elusive. Recent research has focused on the potential of highly conserved regions of the viral hemagglutinin (HA) as targets for broadly neutralizing Ab responses. Abs that bind the highly conserved stem or stalk of HA can be elicited by vaccination in humans and animal models and neutralize diverse influenza strains. However, the frequency and phenotype of HA stem–specific B cells in vivo remain unclear. In this article, we characterize HA stem–specific B cell responses following H5N1 vaccination and describe the re-expansion of a pre-existing population of memory B cells specific for stem epitopes. This population uses primarily, but not exclusively, IGHV1-69–based Igs for HA recognition. However, within some subjects, allelic polymorphism at the ighv1-69 locus can limit IGHV1-69 immunodominance and may reduce circulating frequencies of stem-reactive B cells in vivo. The accurate definition of allelic selection, recombination requirements, and ontogeny of neutralizing Ab responses to influenza will aid rational influenza vaccine design.